Extracellular Vesicles Can Deliver Anti-inflammatory and Anti-scarring Activities of Mesenchymal Stromal Cells After Spinal Cord Injury - Romanelli, Pasquale; Bieler, Lara; Scharler, Cornelia; Pachler, Karin; Kreutzer, Christina; Zaunmair, Pia; Jakubecova, Dominika; Mrowetz, Heike; Benedetti, Bruno; Rivera, Francisco J.; Aigner, Ludwig; Rohde, Eva; et al. (Frontiers in Neurology, 2019)
Spinal cord injury is characterized by an initial neural tissue disruption triggering secondary damage and extensive non-resolving inflammation, which aggravates loss of function and hinders recovery. The early onset of inflammation following traumatic spinal cord injury underscores the importance of acute intervention after the initial trauma. Injections of mesenchymal stromal cells (MSCs) can reduce inflammation following spinal cord injury. We asked if extracellular vesicles (EVs) can substitute anti-inflammatory and anti-scarring activities of their parental MSCs in a rat model of contusion spinal cord injury. We report that MSC-EVs were as potent as the parental intact cells in reducing the level of neuroinflammation for up to two weeks post-injury. Acute application of EVs after spinal cord injury was shown to robustly decrease the expression of pro-inflammatory cytokines in the spinal cord parenchyma in the very early phase of secondary damage. Moreover, the anti-scarring impact of MSC-EVs was even more efficient than the parental cells. We therefore conclude that anti-inflammatory and anti-scarring activities of MSCs application can be mediated by their secreted EVs. In light of their substantial safety and druggability advantages, EVs may have a high potential as early therapeutic following traumatic spinal cord injury.